Exiles and presences between Nicaragua and Costa Rica - Araya, German Chacón (2021)
As a result of 1948 Civil War in Costa Rica, losers and communist militants chose to exile in Nicaragua. Before Sandinist Revolution (1979), many antiSomocists Nicaraguans decided also to exile in Costa Rica. Consequently, we must consider exile as a process of search for power and ideological confrontation.